2010
DOI: 10.1590/s0100-204x2010001100010
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation, postharvest maturity and seed aging of tall oat-grass

Abstract: -The objectives of this work were to determine whether and at which seed physiological maturity stage the diquat desiccant affects the tall oat-grass (Arrhenatherum elatius) seed quality and yield, as well as the proper storage period between harvest and sowing. Diquat desiccation was evaluated in applications during milk or dough seed maturation stages. Seeds conventionally produced and stored under traditional storage conditions were used for the analyses. Seed samples were drawn every 30 th day after harves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Dormancy causing reduced germination immediately after harvest was also present in seeds of other fodder grasses conventionally dried. For instance, 31% of dormant seeds present in Arrhenatherum elatius resulted in germination of 57% (Stanisavljević et al 2010b), while seed germination in Lolium multiflorum, Dactylis glomerata and Phleum pretense amounted to 58, 52 and 62%, respectively (Stanisavljević et al 2011). Very low seed germination (about 50%) was recorded in Brachiaria brizantha (Dias and Toledo 1993), but the dormancy in these seeds if exposed to the temperature of 70°C for 10 and 15 min would be reduced and germination would be increased without adverse effects on physiological quality of seeds (Martins and Silva 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Dormancy causing reduced germination immediately after harvest was also present in seeds of other fodder grasses conventionally dried. For instance, 31% of dormant seeds present in Arrhenatherum elatius resulted in germination of 57% (Stanisavljević et al 2010b), while seed germination in Lolium multiflorum, Dactylis glomerata and Phleum pretense amounted to 58, 52 and 62%, respectively (Stanisavljević et al 2011). Very low seed germination (about 50%) was recorded in Brachiaria brizantha (Dias and Toledo 1993), but the dormancy in these seeds if exposed to the temperature of 70°C for 10 and 15 min would be reduced and germination would be increased without adverse effects on physiological quality of seeds (Martins and Silva 2001).…”
Section: Resultsmentioning
confidence: 99%
“…However, little data has been gathered on physiological mechanisms regulating reduced radicle growth during seed ageing. Studies on leading forage grasses of the genus Festuca and Arrhenatherum elatius also showed that the period of poorer seed germination is followed by a weaker growth of the embryonic shoot, radicle and seedling weight (STANISAVLJEVI et al, 2010a;2010c).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, current seed trading regulations in the Southeastern European countries require a germination rate that exceeds 70%. Currently the germination rate of tall oatgrass (Arrhenatherum elatius) is 63% (Stanisavljević et al, 2010a), that of Italian ryegrass (Lolium multiflorum) is 66%, that of cocksfoot (Dactylis glomerata) is 57% (Stanisavljević et al, 2011), and that of meadow fescue (F. pratensis) is approximately 63% (Stanisavljević et al, 2010b). These germination rates prevent commercial sale of the seed in southeastern Europe.…”
Section: Methodsmentioning
confidence: 99%
“…According to the conclusions of Stanisavljević et al (2010aStanisavljević et al ( , 2010bStanisavljević et al ( , 2011 and Rozman et al (2010), increased rates of germination of seeds of perennial forage grasses is accompanied by increased seedling vigour. A high rate of seed germination this creates conditions for successful establishment of grass species when competing with weeds and other species found in mixtures of seeds.…”
Section: Sheep Fescuementioning
confidence: 99%